Theory on the Propagation of UHF Radio Waves in Coal Mine Tunnels - Alfred G. Exslie; Robert L. Lagace; Peter F. Strong (The National Institute for Occupational Safety and Health (NIOSH), 1974)
The theoretical study of WF radio communication in coal mines, with particular reference to the rate of loss of signal strength along a tunnel, and from one tunnel to another around a comer is the concern of this paper. Of prime interest are the nature of the propagation mechanism and the prediction of the radio frequency that propagates with the smallest loss. The theoretical results are compared with published measurements. This work was part of an investigation of new ways to reach and extend two-way communications to the key individuals who are highly mobile within the sections and haulageways of coal mines.